Detection of paraquat in calliphorid maggots by capillary electrophoresis for diagnosing fatal poisoning - Kamarudin, Rosaniza (2015)
Entomotoxicology deals with the identification and quantitation of drugs and poisons in maggots for the purpose of diagnosing the possible cause of death, especially in highly decomposed bodies wherein the conventional toxicological specimens are not suitable or available for sampling. In this context, poisons such as paraquat have been reported as one of the agents used for committing suicides as well as accidental deaths and hence the use of Calliphorid maggots for toxicological analysis has been suggested. However, specific analytical method for analyzing paraquat in maggots remains unreported and in view of this problem, this present study that aimed to develop such method acquires forensic significance. The third instar of Calliphorid larvae that fed on paraquat-treated beef substrates in lethal dose for human (sample P1; 40 mg/kg) and three times the lethal dose (sample P2; 120 mg/kg) were collected and extracted using protein precipitation technique. Samples (0.4 g) were mixed with formic acid and ultrapure water, centrifuged and filtered. Paraquat residue was analysed using capillary zone electrophoresis with diode array detector (CZE-DAD). CZE analysis was performed in fused silica capillary under potential +25 kV and detection at 195 nm. The electrolyte was a 50 mM phosphate buffer at pH 2.50. Results of this study indicated that the presence of paraquat was detected in Calliphorid maggot samples that were collected from the paraquat-treated beef substrates in less than 2.5 mins under the optimized conditions and proved the reliability of these samples for qualitative analyses; LOD and LOQ were 0.495 µg/mL and 1.501 µg/mL, respectively. Detection of paraquat in maggots may prove useful in diagnosing the cause of death, since paraquat is a poison compared to other drugs of abuse.